Older adults recover more marginal knowledge and use feedback more effectively than younger adults: evidence using “I don’t know” vs. “I don’t remember” for general knowledge questions - Umanath, Sharda; Barrett, Talia E.; Kim, Stacy; Walsh, Cole A.; Coane, Jennifer H. (Frontiers in Psychology, 2023)
Through three experiments, we examined older and younger adults’ metacognitive ability to distinguish between what is not stored in the knowledge base versus merely inaccessible. Difficult materials were selected to test this ability when retrieval failures were very frequent. Of particular interest was the influence of feedback (and lack thereof) in potential new learning and recovery of marginal knowledge across age groups. Participants answered short-answer general knowledge questions, responding “I don’t know” (DK) or “I don’t remember” (DR) when retrieval failed. After DKs, performance on a subsequent multiple-choice (Exp. 1) and short-answer test following correct-answer feedback (Exp. 2) was lower than after DRs, supporting self-reported not remembering reflects failures of accessibility whereas not knowing captures a lack of availability. Yet, older adults showed a tendency to answer more DK questions correctly on the final tests than younger adults. Experiment 3 was a replication and extension of Experiment 2 including two groups of online participants in which one group was not provided correct answer feedback during the initial short-answer test. This allowed us to examine the degree to which any new learning and recovery of access to marginal knowledge was occurring across the age groups. Together, the findings indicate that 1) metacognitive awareness regarding underlying causes of retrieval failures is maintained across different distributions of knowledge accessibility, 2) older adults use correct answer feedback more effectively than younger adults, and 3) in the absence of feedback, older adults spontaneously recover marginal knowledge.